Sampling and Detection Strategies for the Pine Pitch Canker (PPC) Disease Pathogen Fusarium circinatum in Europe - Vainio, Eeva; Bezos, Diana; Bragança, Helena; Cleary, Michelle; Fourie, Gerda; Georgieva, Margarita; Ghelardini, Luisa; Hannunen, Salla; Ioos, Renaud; Martín-García, Jorge; Martínez-Álvarez, Pablo; Mullett, Martin; et al. (MDPI AG, 2019)
Fusarium circinatum Nirenberg & O’Donnel is listed among the species recommended for regulation as quarantine pests in Europe. Over 60 Pinus species are susceptible to the pathogen and it also causes disease on Douglas-fir (Pseudotsuga menziesii (Mirb.) Franco) and species in genera such as Picea and Larix. The European Food Safety Authority considers the probability of new introductions—via contaminated seeds, wood material, soil and growing substrates, natural means and human activities—into the EU very likely. Due to early detection, constant surveillance and control measures, F. circinatum outbreaks have officially been eradicated in Italy and France. However, the global spread of F. circinatum suggests that the pathogen will continue to be encountered in new environments in the future. Therefore, continuous surveillance of reproductive material, nurseries and plantations, prompt control measures and realistic contingency plans will be important in Europe and elsewhere to limit disease spread and the “bridgehead effect”, where new introductions of a tree pathogen become increasingly likely as new environments are invaded, must be considered. Therefore, survey programs already implemented to limit the spread in Europe and that could be helpful for other EU countries are summarized in this review. These surveys include not only countries where pitch canker is present, such as Portugal and Spain, but also several other EU countries where F. circinatum is not present. Sampling protocols for seeds, seedlings, twigs, branches, shoots, soil samples, spore traps and insects from different studies are collated and compiled in this review. Likewise, methodology for morphological and molecular identification is herein presented. These include conventional PCR with a target-specific region located in the intergenic spacer region, as well as several real-time PCR protocols, with different levels of specificity and sensitivity. Finally, the global situation and future perspectives are addressed.
Keywords: Gibberella circinata; quarantine species; damping-off; survey programs; morphological identification; molecular detection